IMPLEMENTASI PENDEKATAN BOTTOM-UP DALAM PERENCANAAN PEMBANGUNAN DESA DI KECAMATAN TUMPAAN KABUPATEN MINAHASA SELATAN - legi, Riedel; Rompas, Wilson Y; Pombengi, Jericho D (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRAKThis study aims to determine how the Implementation of Bottom-Up Approach inRural Development Planning in The Subdistrict Tumpaan South Minahasa District, alsoto determine the extent of Implementation of Bottom-Up Approach in RuralDevelopment Planning can encourage community participation in rural development inSub Tumpaan South Minahasa District,In the methods used in this research is descriptive-qualitative method. Researchconducted in four villages that was taken from 10 villages in the District Tumpaan.Informant studies taken from various related elements, namely The Village Head, BPD,LPM, and Leaders/ Community Leaders entirety as many as 16 people. Date collectionusing interview techniques. The analysis technique used is qualitative analysisinteractive models of Miler and Hubermann.Based on the research result deduced: (1) Implementation of a bottom-upapproach to development planning in the village has been able to do well in the village inthe subdistrict Tumpaan; (2) Implementation of bottom-up approach the planning ofRural Development must be supported by harmonious cooperation between the relevantinstitution; (3) The implementation of bottom-up approach the Rural Developmentplanning is also supported by the participation of the entire communityKeyword : Bottom-Up Approach, Rural Development Planning